Application progress of conductive conjugated polymers in electromagnetic wave absorbing composites. (August 2021) - Lan, Di; Gao, Zhenguo; Zhao, Zehao; Kou, Kaichang; Wu, Hongjing
Abstract: With the rapid development of electronic communication technology, electromagnetic (EM) wave plays an important role in transmitting energy and information. However, in this process, a lot of redundant EM radiation always threatens the stability of electronic equipment and human health. EM wave absorbing materials (EMWAs) play an important role in absorbing EM pollution and military stealth. Therefore, a variety of different types of EM wave absorbing materials have been developed rapidly at the same time. Among them, CP based absorbing materials have attracted extensive attention due to their low density, high mechanical, wear resistance, corrosion resistance, adjustable electrical properties and other characteristics. In this review, several representative types of CP based absorbing materials, such as polyaniline (PANI), PPy (PPy), polythiophene (PTh), are the main research objects. The development status of CP based absorbing materials in recent years are summarized, including the related preparation process, characterization methods and absorption mechanisms. Finally, the development prospects of advanced CP based absorbers are prospected. Highlights: Several representative CPs (PANI, PPy, PTh, etc.) were selected as the main research objects. The application, absorption mechanisms of CPs absorbers were summarized. Prospects and shortcomings of CPs as EMWAs were summarized in detail.